1996
DOI: 10.1007/bf02735453
|View full text |Cite
|
Sign up to set email alerts
|

The influence of repeated motherhood on periparturitional behavior in cynomolgus macaques (Macaca fascicularis)

Abstract: We studied the influence of parity on periparturitional behavior by quantitativelY comparing the behavior of 10 primiparous and 11 multiparous cynomolgus macaques. We found a considerable number of significant differences, some of them affirming the outcome of previous descriptive studies. During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
19
2
Order By: Relevance
“…Like rhesus (Brandt and Mitchell, 1971), pigtailed (Goodlin and Sackett, 1983), and most other macaques (Jolly, 1972), cynomolgus macaques generally give birth at night (Suzuki et al, 1990;Timmermans and Vossen, 1996). When the natural circumstances are borne in mind, the adequacy of investigating the anogenital zone and supporting the neonate at birth is obvious.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like rhesus (Brandt and Mitchell, 1971), pigtailed (Goodlin and Sackett, 1983), and most other macaques (Jolly, 1972), cynomolgus macaques generally give birth at night (Suzuki et al, 1990;Timmermans and Vossen, 1996). When the natural circumstances are borne in mind, the adequacy of investigating the anogenital zone and supporting the neonate at birth is obvious.…”
Section: Discussionmentioning
confidence: 99%
“…The mother has to bring the infant into ventroventral position, whereby the neonate is nestled between the mother's thighs and arms, pro-viding her an opportunity to lick herself and the neonate and to handle the placenta (Timmermans and Vossen, 1996). The ventroventral position gives the infant benefit of the mother's body heat and enables it to reach her teats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers usually did not eat as they usually would for 2-3 days before parturition, which supports the hypothesis that consumption of the placenta provided nutrition and energy to the mothers. Timmermans and Vossen [1996] have reported that multiparous mothers were more skillful and efficient before, during and after the birth than primiparous mothers. However, parity did not seem to affect parturition behaviour in our case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous video data and still photographs were collected throughout the entire parturition process. The parturitions and their associated activities were divided into 3 phases: prepartus, from the first observed onset of labour till the infant became visible in the birth canal; partus, from the time the infant was first visible until it had entirely emerged from the mother's body, and postpartus, from the infant delivery until the consumption of the placenta [Timmermans and Vossen, 1996;Turner et al, 2010]. Scan sampling [Altmann, 1974] was also used to record the location of parturition and the involvement of the group members before, during and after parturition.…”
Section: Data Collectionmentioning
confidence: 99%